Magnetically triggered release of biologics. (17th February 2019) - Lanier, Olivia L.; Monsalve, Adam G.; McFetridge, Peter S.; Dobson, Jon
ABSTRACT: The development of platforms for the controlled release of therapeutic molecules remains a crucial research focus, as controlled release reduces the frequency of administration, minimizes side effects and improves compliance. However, biological conditions and diseases with a progression that exhibits strong temporal dependence, or those that can result in the evolution of tolerance to the therapeutic during continuous exposure, require the development of sophisticated release systems tailored to the needs to the individual and the disease. Thus, there has been emphasis on the development of platforms with remotely controlled release mechanisms. Specifically, magnetically triggered release utilizes magnetic nanoparticles as the remote control modality. Many reviews discuss the magnetically triggered release of small molecule drugs, however, the release of biomacromolecules has not been reviewed. This review examines the limited work on the magnetically triggered release of biomacromolecules and the challenges associated with their delivery. Important material parameters that have been used in this pursuit are discussed.